2018
DOI: 10.1007/s11738-018-2663-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of agricultural weed seed germination by smoke and smoke-derived karrikin (KAR1), with a particular reference to Avena fatua L.

Abstract: Plant-derived smoke, its water extract-the smoke water (SW), and karrikin (KAR 1) present in the smoke stimulate seed germination in plants from fire-prone and fire-free areas, including weeds and cultivated plants. There are also plants, the seeds of which can respond only to smoke, but not to KAR 1 , and vice versa. Smoke and/or KAR 1 can be applied in horticulture, agriculture, and revegetation. This review describes effects of smoke and KAR 1 on weed seed germination and focuses mainly on the recent knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 59 publications
1
21
0
1
Order By: Relevance
“…In addition, the regulatory mechanisms of dormancy status and the germination potential of a seed are postulated to also comprise the other plant hormones, including ethylene, auxins, jasmonates, and brassinosteroids (Linkies and Leubner-Metzger 2012;Corbineau et al 2014). Ethylene has been reported to break primary and secondary dormancy (Kępczyński andKępczyńska 1997, 2003;Corbineau et al 2014). Several studies have shown the correlation between ethylene production and/or action and the ability to germinate (Kępczyński and Kępczyńska 1997;Matilla and Matilla-Vázquez 2008;Corbineau et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the regulatory mechanisms of dormancy status and the germination potential of a seed are postulated to also comprise the other plant hormones, including ethylene, auxins, jasmonates, and brassinosteroids (Linkies and Leubner-Metzger 2012;Corbineau et al 2014). Ethylene has been reported to break primary and secondary dormancy (Kępczyński andKępczyńska 1997, 2003;Corbineau et al 2014). Several studies have shown the correlation between ethylene production and/or action and the ability to germinate (Kępczyński and Kępczyńska 1997;Matilla and Matilla-Vázquez 2008;Corbineau et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, the stimulatory effects of KAR 1 were suppressed in the presence of 2, 5‐norbornadiene (NBD: competitive and reversible inhibitor of ethylene reception) and 1‐methylcyclopropene (1‐MCP: a non‐reversible ethylene inhibitor), thus indicating the necessity of ethylene for the release of dormancy. Application of ethylene after NBD treatment again restored the germination potential in A. fatua caryopses (Kępczyński ). However, treatment of the dormant caryopses with ethylene biosynthetic inhibitors like α‐aminoisobutyric acid and aminoethoxyvinylglycine did not affect the activity of KAR 1 to a notable extent (Kępczyński and Van Staden ).…”
Section: Introductionmentioning
confidence: 92%
“…Along with paclobutrazol, other inhibitors of GA anabolism like ancymidol and flurprimidol also antagonized the germination‐promoting effects of KAR 1 , and this inhibition was released on treatment with GA 3 (Kępczyński et al ). Recent data also revealed that KAR 1 works in synchronization with GA 3 to degrade ABA to phaseic acid in order to induce dormancy release in the seeds of A. fatua (Kępczyński ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, KAR treatment can increase the expression of the GA 3 oxidase gene in Arabidopsis seeds [99]. Inhibitors of GA synthesis had an inhibitory effect on seed germination induced by smoke [175]. KAR 1 and GA 3 synergistically inhibit ABA activity and release seed dormancy [176].…”
Section: Sl or Kar Crosstalk With Gibberellinmentioning
confidence: 99%